Pengaruh Current Ratio,Quick Ratio,Cash Ratio,Debt To Equity Ratio Dan Sales Growth Terhadap Profitabilitas Perusahaan Aneka Industri Yang Terdaftar Di BEI Tahun 2017-2018 - Ninta Mitokona Banurea; Gita Febry Yanti Simatupang; Friska Darnawaty Sitorus; Monetarist Butar Butar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the relationship between financial parameters and profitability of companies in various industries listed on the Indonesia Stock Exchange between 2017 and 2019. Profitability is the dependent variable in this study, while debt to equity ratio, current ratio, quick ratio, cash ratio, and sales growth are independent factors. The research sample used is purposive sampling, and the following standards are used: (1) companies listed on the Indonesia Stock Exchange; (2) various industrial enterprises; and (3) businesses that have comprehensive annual financial statements for 2017 to 2019. Through sampling, 25 businesses from various industries were identified as meeting these criteria. The results of the regression analysis stated that the current ratio, quick ratio, and cash ratio did not have a significant effect on the company's profitability. However, debt to equity ratio and sales growth have a significant influence on a company's profitability. Thus, it can be said that the use of financial ratios such as debt to equity ratio and sales growth can increase profitability for the company. This research has several practical implications for companies in various industries, namely companies can consider the use of debt to equity ratio and sales growth in making strategic decisions to increase profitability. However, it can be noted that the results of this study are only valid in the specified research period, so companies need to conduct follow-up research to ensure the use of appropriate financial ratios in the long term Keywords: Current Ratio,Quick Ratio,Cash Ratio,Debt To Equity Ratio,And Sales Growth